2022
DOI: 10.1021/acsami.2c03575
|View full text |Cite
|
Sign up to set email alerts
|

Humidity-Tolerant Chemiresistive Gas Sensors Based on Hydrophobic CeO2/SnO2 Heterostructure Films

Abstract: The accelerated evolution of the Internet of Things has brought new challenges to the gas sensors, which are required to work persistently under harsh conditions, like high humidity. However, currently, it is quite challenging to solve the hindrance of the trade-off between gas-sensing performance and anti-humidity ability of the chemiresistive gas sensors. Herein, hydrophobic inorganic CeO 2 /SnO 2 heterostructure films were prepared by depositing the CeO 2 layers with a thickness of a few nanometers onto the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(32 citation statements)
references
References 60 publications
0
26
0
Order By: Relevance
“…Under the same humidity, the responses of all gas sensors first increase gradually to the maximum values and then fall off to smaller values by degrees with the increase of working temperature. It is associated with the adsorption–desorption kinetics of the isopropanol molecules . Generally, the diffusion rates of isopropanol molecules increase as the working temperature increases, resulting in more amount of isopropanol molecules adsorbed on the surface of the sensing materials.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Under the same humidity, the responses of all gas sensors first increase gradually to the maximum values and then fall off to smaller values by degrees with the increase of working temperature. It is associated with the adsorption–desorption kinetics of the isopropanol molecules . Generally, the diffusion rates of isopropanol molecules increase as the working temperature increases, resulting in more amount of isopropanol molecules adsorbed on the surface of the sensing materials.…”
Section: Resultsmentioning
confidence: 99%
“…5 In addition, Pt@ZnIn 2 has a higher percentage of O II , which can provide more oxygen adsorption sites associated with the high gas response. 33 Generally, the diffusion rates of isopropanol molecules increase as the working temperature increases, resulting in more amount of isopropanol molecules adsorbed on the surface of the sensing materials. However, when the working temperature is beyond a threshold (optimal working temperature), the desorption process of isopropanol molecules dominates, leading to the deterioration of the sensing reaction and the recession of the response value.…”
Section: Materials Characterization Figurementioning
confidence: 99%
“…Moreover, a large number of oxygen species are adsorbed at the interface of n–n heterojunctions. , In addition, when the BiOBr/ZnO sensor is exposed to TEA, TEA will react with oxygen anions and release electrons, which narrows the EDL and reduces the resistance value. In a word, compared with ZnO and BiOBr, the BiOBr/ZnO sensor presents a more significant resistance change during TEA sensing, resulting in a higher response …”
Section: Results and Discussionmentioning
confidence: 99%
“…In a word, compared with ZnO and BiOBr, the BiOBr/ZnO sensor presents a more significant resistance change during TEA sensing, resulting in a higher response. 46 Finally, as investigated by EPR, oxygen vacancies play an important role in the TEA sensing performance. Hou et al also reported that oxygen vacancies can be of immense benefit to the gas-sensitive properties.…”
Section: Gas Sensitivity Mechanismmentioning
confidence: 99%
“…In practical applications, the changes in ambient humidity will have a greater impact on the performance stability (sensitivity and response/recovery speed) and freshness assessment accuracy of TEA gas sensors, especially for devices with lower operating temperatures. To solve such problems, Zhu et al prepared hydrophobic inorganic CeO 2 /SnO 2 heterostructure films gas sensors, demonstrating excellent gas-sensing properties to TEA with high response, wide detection range (0.04-500 ppm), low detection limit (0.04 ppm), and long-term stability, while possessing promising anti-humidity sensing ability (Zhu et al, 2022). Xiong et al synthesized two-dimensional ultrathin ZnO/Co 3 O 4 heterostructure nanomeshes by in situ growth technology (Xiong et al, 2021).…”
Section: Triethylaminementioning
confidence: 99%